1979
DOI: 10.1038/bjc.1979.115
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and in-situ natural killer activity in tumour-bearing rats

Abstract: Summary.-Single-cell suspensions prepared by enzymatic disaggregation of an immunogenic 3-methylcholanthrene-induced sarcoma (Mc4OA) contain a significant proportion of infiltrating leucocytes (42%) comprising T lymphocytes, macrophages and non-phagocytic FcR+ lymphoid-like cells. Tumour-infiltrating lymphocytes (TIL) were isolated and purified by successive passage over Sephadex G-10 columns and their cytotoxic activity in vitro compared with that of lymphoid cells from normal rats and from tumour-bearers at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Tumor cells contaminating tumor-infiltrating lymphocytes have been thought to account for the depression of NK activity in rat sarcoma [14]. The lack of NK activity of effusion lymphocytes could be attributed to contaminating tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells contaminating tumor-infiltrating lymphocytes have been thought to account for the depression of NK activity in rat sarcoma [14]. The lack of NK activity of effusion lymphocytes could be attributed to contaminating tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that the inhibitor cells could be removed from splenocyte suspensions by passage through G-10 Sephadex columns. These Sephadex-adhering NK inhibitor cells could be either tumor cells (Moore and Moore, 1979), or macrophage-like cells (Padarathsingh et al, 1979). It is important to note that Sephadex-adhering cells constitute a majority, within the spleen of tumor bearers (60% or more) whereas only 10-20% of normal splenocytes express this charcteristic.…”
Section: N K Activity and Cytostatic Activities Mediated By Splenocytmentioning
confidence: 99%
“…Mononuclear leucocytes were recovered from the gradient interface and lymphocytes purified by passage down a Sephadex GIO column as described by . This procedure has been shown to enrich for a "natural killer" lymphocyte population in rodent tumours (Moore & Moore, 1979) and human peripheral blood (Mantovani et al, 1979). PMNL were recovered from the FT gradient pellet after removing the erythrocytes by sedimentation through a Dextran gradient (Boyiim, 1968 (1-3-42.3 x 106 total) as was the proportion of the major free lung cell types: BAM, lymphocytes and PMNL (Table).…”
mentioning
confidence: 99%